2023
DOI: 10.1093/evolut/qpad098
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of reproductive isolation in a long-term evolution experiment with Drosophila melanogaster: 30 years of divergent life-history selection

Abstract: We ask if three decades and over 1 500 generations of divergent life history selection on age at reproduction has resulted in the evolution of reproductive isolation (RI) between laboratory populations of Drosophila melanogaster. We tested for premating, postmating-prezygotic and postzygotic reproductive isolation between 3 replicate population pairs. Large, evolved differences in body size between selection treatments suggested the potential for prezygotic barriers driven by sexual selection or physical incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
0
0
Order By: Relevance
“…Positive assortative mating (hereafter, assortative mating), wherein genotypic or phenotypic trait values are positively correlated between mates, has been empirically observed across animal species ( Jiang et al 2013 ). Theoretical and empirical studies have demonstrated the consequences of assortative mating for speciation and hybridization ( Kondrashov 1983 ; Otto et al 2008 ; Tung et al 2012 ; Schumer et al 2017 ; Kopp et al 2018 ; Powell et al 2021 ; Muralidhar et al 2022 ; Natola et al 2022 ; Smadja et al 2022 ; Robinson et al 2023 ), and for the distributions of traits within populations ( Wright 1921 ; Norris et al 2019 ; Kim et al 2021 ; Border et al 2022 ; Muralidhar et al 2022 ; Horwitz et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Positive assortative mating (hereafter, assortative mating), wherein genotypic or phenotypic trait values are positively correlated between mates, has been empirically observed across animal species ( Jiang et al 2013 ). Theoretical and empirical studies have demonstrated the consequences of assortative mating for speciation and hybridization ( Kondrashov 1983 ; Otto et al 2008 ; Tung et al 2012 ; Schumer et al 2017 ; Kopp et al 2018 ; Powell et al 2021 ; Muralidhar et al 2022 ; Natola et al 2022 ; Smadja et al 2022 ; Robinson et al 2023 ), and for the distributions of traits within populations ( Wright 1921 ; Norris et al 2019 ; Kim et al 2021 ; Border et al 2022 ; Muralidhar et al 2022 ; Horwitz et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%